An ADAMTS13 mutation that causes hereditary thrombotic thrombocytopenic purpura: a case report and literature review - Pengzhu Li; Jie Jiang; Qiong Xi; Zuocheng Yang (BMC, 2021)
Abstract Background Mutations in the ADAMTS13 gene can lead to an ADAMTS13 enzyme deficiency, which is related to Upshaw-Schulman syndrome (USS). USS is a common type of thrombotic thrombocytopenic purpura (TTP). Here we present a very rare case of TTP caused by 2 mutations in the ADAMTS13 gene. Besides, we reviewed and summarized previous pathogenic ADAMTS13 gene mutations associated with the TTP. Case presentation A 10-year-old female was admitted to the Third Xiangya Hospital of Central South University after experiencing discontinuous thrombocytopenia for 8 years, abnormal renal function for more than 2 years, cough for more than 10 days, and weakness of the left limb for 3 days. Gene sequencing shows the patient's ADAMTS13 gene contains compound heterozygous nucleotide variations: c.1335delC (p. Phe445LeufsTer52) is a frameshift variation inherited from her father and c.2130C > G (p. Cys710Trp) is a missense variation inherited from her mother. The final diagnosis was USS. Conclusions Our study reports a very rare genetic TTP case caused by two compound heterozygous variants in the ADAMTS13 gene. The effect of these two mutations on the secretion of ADAMTS13 requires further in vitro experiments to confirm.